Synthesis of chiral 4, 5-dihydrothiazol-2-amines and 4, 5-dihydrooxazol-2-amines through an unexpected ring opening reaction of azetidines. Issue 11 (16th March 2016) - Zhou, Xin; Xu, Xingyu; Li, Yi; Zhang, Zhanbin; Zheng, Zhi-bing
Graphical abstract: Abstract: A general and concise new method to the synthesis of chiral 4, 5-dihydrothiazol-2-amines and 4, 5-dihydrooxazol-2-amines has been developed. Chiral 4, 5-dihydrothiazol-2-amines were made from the reaction of chiral 3-amino-4-aryl-azetidines with isothiocyanates via a completely regio- and stereoselective ring opening reaction of azetidines. And chiral 4, 5-dihydrooxazol-2-amines were synthesized by the isomerization of the urea intermediates in the presence of TFA.